UV-Visible studies of chemical bath deposited Ni3Pb2S2 films - Ho, Soon Min (2015)
Ni3Pb2S2 thin films have been prepared under various deposition times. The films were characterized using UVVisible spectrophotometer. The obtained results indicated that the strong absorption in the visible regions. On the other hand, it is seen that the band gap was increased from 1.1 to 1.4 eV as the deposition time was reduced from 55 to 25 minutes.